Monitoring Health Protocols Covid-19 In Public Facilities - Eli Marlina Lubis; Lidya Hariyanti Ridho; Sherien Sakina Wira Wasistha; Sri Bulan Suci Ritonga (Pena Cendekia Insani, 2022)
Covid-19 is a problem that has not been resolved for three years. The implementation of the health protocol is one of the efforts to stop the spread of COVID-19, especially in public facilities where this is a place where people gather. The purpose of the study was to find out the description of the application of health protocols in public facilities. Method: This type of quantitative descriptive research. The study was conducted in public facilities in the DKI Jakarta, Riau, North Sumatra and surrounding areas in June-August 2021. The population of all public facilities with a sample of 40 public facilities. Result: Based on the results of the study, it was still found that public facilities had no warnings for the dangers of COVID-19 (55%), no hand sanitiser (60%) and nobody temperature measuring device (53%), no call for the social distancing of (53%). 60%) and cleaning with disinfectant was not carried out (64%). Some visitors did not wear masks (51%). Managers of public facilities were found not to take body temperature measurements (65%), there was no restriction on the number of visitors (70%). Conclusion: Implementing health protocols requires awareness and cooperation from all parties, not only the Government. Therefore, be aware and continue to educate the public regarding the prevention of the spread of COVID-19 to reduce the number of cases and carry out normal activities.